Polyaniline on Stainless Steel Fiber Felt as Anodes for Bioelectrodegradation of Acid Blue 29 in Microbial Fuel Cells - Khan, Mohammad Danish; Tabraiz, Shamas; Thimmappa, Ravikumar; Li, Da; Anwer, Abdul Hakeem; Scott, Keith; Khan, Mohammad Zain; Yu, Eileen Hao (Frontiers in Chemical Engineering, 2022)
This study investigated the advantages of using a low-cost polyaniline-fabricated stainless steel fiber felt anode-based microbial fuel cells (PANI-SSFF-MFCs) for azo dye acid blue 29 (AB29) containing wastewater treatment integrated with an aerobic bioreactor. The findings of electrochemical impedance spectroscopy (EIS) and polarization studies showed that the PANI–SSFF anode considerably decreased the MFC internal resistance. The highest power density of 103±3.6 mW m−2 was achieved by PANI-SSFF-MFC with a decolorization efficiency of 93±3.1% and a start-up time of 13 days. The final chemical oxygen demand (COD) removal efficiencies for integrated PANI–SSFF–MFC–bioreactor and SSFF–MFC–bioreactor set-ups were 92.5±2% and 80±2%, respectively. Based on 16S rRNA gene sequencing, a substantial microbial community change was observed in MFCs. The majority of sequences were from Proteobacteria phylum, accounting for 72% and 55% in PANI–SSFF–anodic biofilm and suspension and 58% and 45% in SSFF–anodic biofilm and suspension, respectively. The relative abundance of the seven most abundant genera (Pseudomonas, Acinetobacter, Stenotrophomonas, Geothrix, Dysgonomonas, Shinella, Rhizobiales) was higher in PANI–SSFF–MFC (46.1% in biofilm and 55.4% in suspension) as compared to SSFF–MFC (43% in biofilm and 40.8% in suspension) which predominantly contributed to the decolorization of AB29 and/or electron transfer. We demonstrate in this work that microbial consortia acclimated to the MFC environment and PANI fabricated anodes are capable of high decolorization rates with enhanced electricity production. A combined SMFC-aerobic bioreactor operation was also performed in this study for the efficient biodegradation of AB29.